Role of antioxidant additives in the protection of DNA integrity of buck spermatozoa with RAPD assay - SARASWAT, SONIA; JINDAL, S K; KHARCHE, S D; ROUT, P K; RANJAN, R; PRIYADHARSINI, R (The Indian Journal of Animal Sciences, 2014)
The role of antioxidants (reduced glutathione, ascorbic acid and α-tocopherol) on DNA integrity with the random amplified polymorphic DNA (RAPD) was studied. This assay relies on presence or absence of amplification product on ethidium bromide stained agarose gels. The size of amplification products ranged from 190 to 1,900 base pair. Antioxidants effectively protect sperm DNA from damage. Moreover, random amplified polymorphic DNA technique can be used for the studies of the molecular seminal characteristics of buck semen.